Embracing differences in virtual reality: inclusive user-centered design of bimanual interaction techniques - Hartfill, Judith; Hajahmadi, Shirin; Schmidt, Susanne; Marfia, Gustavo; Steinicke, Frank (Frontiers in Virtual Reality, 2025)
IntroductionVirtual Reality (VR) applications often require two-handed interactions, which can pose accessibility challenges for users with missing limbs or limited mobility in the arms or hands. This paper investigates how to make bimanual input more accessible and inclusive using electromyography and motion tracking.MethodsThrough an inclusive user-centered design approach, we developed three interaction techniques after interviewing a person with unilateral upper limb differences. To assess baseline metrics on the efficiency and usability of the three prototypes, a user study was conducted with 26 participants without upper limb differences.Results, discussion, study 1 We found that those interaction methods can be as efficient as unimanual interactions, even without prior learning, showing the potential of electromyography and motion tracking for bimanual interaction in VR.Methods study 2In a second user study, feedback was gathered from four participants with unilateral upper limb impairments to refine the interaction techniques and identify accessibility barriers in the design.Results and discussion study 2Results of the thematic analysis indicate that people with upper limb differences enjoyed the proposed bimanual interaction techniques, while they suggested improvements in ergonomics and system stability.